Influence of the ball speed on the displacement of the center of gravity during baseball batting motion - Tago, T.; Kaneko, K.; Tsuchioka, D.; Ishii, N.; Wada, T. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate the modification in batting motion with different pitching speeds focusing on differences in batting technical level. The subjects were 10 experienced university baseball player. The subjects batted toward the center field, both fastballs and slowballs, aimed near the center of the strike zone from a pitching machine. Data were collected using a three dimensional automatic motion analysis system (Vicon MX). The displacement of the center of gravity(CG) were computed. Significant differences were seen due to difference in pitching speed in unskilled player. Conversely, in skilled player, no significant difference was found in the movement of CG due to the difference in pitching speed. It was revealed that it was not preferable for movement of the CG to fluctuate by difference in pitching speeds.